Experimental study of fouling process and antifouling effect in convective heat transfer under ultrasonic treatment. (25th July 2018) - Hou, Tengfei; Chen, Yongchang; Wang, Zepeng; Ma, Chongfang
Highlights: A dynamic fouling monitor system with an ultrasonic device was set up. The hard water was treated by ultrasound during convective heat transfer process. The crystal morphology of calcium carbonate was observed by microscope. The shape factor was analyzed for crystal nucleation. Abstract: An experimental study was carried out by a dynamic fouling monitor system to investigate the fouling process in convective heat transfer by ultrasonic treatment. During the experiment, the cooling water in heat exchanger was used as working fluid with the inlet temperature of 22.5 °C and 44 °C and the initial hardness of 300 mg/L and 500 mg/L, respectively. For all cases the inlet temperature of hot water was kept at 70 °C, and the flowrates of cooling water and hot water were set at 0.77 m 3 /h and 0.81 m 3 /h, respectively. In this experimental setup, a double-tube heat exchanger was served as a test section of heat transfer, in which hot water flows inside the inner copper tube and cooling water flows in the annular gap between the two tubes, thus forming a counter-flow situation. Further, an ultrasonic device was installed for water treatment with a frequency of 20.7 kHz and power ranging from 0 to 75 W. The results showed that the fouling resistance for hard water increased evidently with increasing of water temperature and hardness. With the ultrasonic treatment, the fouling resistance decreased remarkably compared with the untreated case, and the asymptotic fouling resistance decreased monotonously with increasing of the ultrasonic power. Subsequently, the crystal morphology of calcium carbonate was observed in microscopic view and the transform of crystal from the vaterite to aragonite and calcite was analyzed based on the theory of the formation energy. It was confirmed that the ultrasonic treatment may have significant effect on the crystal shape, and more aragonites appeared with increasing powers of ultrasound.